Students’ perception of oral corrective feedback in speaking classes - Asnawi Muslem; Teuku Zulfikar; Inas Astila (Universitas Syiah Kuala, 2017)
This survey was aimed at finding out students’ perceptions towards lecturers’ oral corrective feedback in speaking classes. This survey involved 100 fourth semester students of the Department of English Language Education at Ar-Raniry State Islamic University (UIN Ar-Raniry) in Banda Aceh. They were randomly chosen to fulfil the estimated population needed for the survey sample. A modified questionnaire from Calsiyao (2015) and Elsaghayer (2014) was used to collect the data. The results showed that the students perceived the lecturers’ oral corrective feedback as an important part of language learning. The lecturers’ oral corrective feedback was very helpful in improving the speaking ability of the students.